PERANCANGAN PROYEK POSH AVENUE HIGH-END SHOPPING CENTER AND EATERY DENGAN PENDALAMAN PARAMETRIC DESIGN OLEH KONSULTAN ARSITEKTUR OSHU STUDIO - Celine Gojono; Stephanus Evert Indrawan (KREASI, 2023)
The production of design and work has completely changed in the digital age. Building design is beginning to incorporate digital architecture as a common technology. Located in Surabaya, Indonesia, Oshu Studio is an architectural consulting firm that constantly innovates in its industry to become the greatest. In the modern era, elevating digital architecture as a benefit is still extremely rare. Oshu Studio chose to adopt a parametric design for this design because it recognized the swift advancement of technology, which is particularly important given the prevalence of quick technological advancements. The Posh Avenue project’s aim, among other things, is to provide solutions to clients’ problems or needs by designing a building Shopping Center and an eatery that can increase sales and bring digital architectural trends to the people of Surabaya City has never existed before. The digital architectural concept adopted by Oshu Studio to realize the client’s wishes is using a Kinetic Facade. The use of digital technology produces design outcomes that are distinct and give off the client’s desired futuristic vibe. In addition, the Avenue High-End Shopping Center and Eatery project is designed with great efficiency in terms of time. Apart from that, the most significant factor is that Oshu Studio can explain and exhibit simulations more easily using digital architectural software.